The Effect of Village Income, Village Funds and Village Allocation of Funds on Village Expenditures in Indonesia - Hastuti, Indra; Putri, Andhita Kusuma; Destiana, Tesa Frida (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
The implementation of Law Number 6 of 2014 concerning Villages is a new milestone in increasing village independence. In the current era where the Law on Villages has just been implemented, there is still a lack of research on the implementation of the Village Law, especially how the influence of Village Opinions (PADes), Village Funds (DD), Village Fund Allocations (ADD) and Tax and Retribution Sharing BHPR) for the allocation of Village Expenditures, especially in the field of public works (BDPU).The handover of autonomy rights provides an opportunity for the village administration to carry out village development. Village development can be realized if development activities are budgeted in village expenditures which are funded using village income sources consisting of village original income (Padesa), transfer income, and other income.